THE IMPACT OF E-COMMERCE TOWARD CONSUMER PURCHASE INTENTION AT UD.CIPTA PRIMA MEDAN - Hengky Kosasih; Benny Lim; Yenni; Eddy; Ali Syah Putra (Jurnal Cakrawala Ilmiah, 2022)
This study empirically examines the website attributes in ecommerce influencing customer purchase intention. The writer do the observation and preliminary data that UD. Cipta Prima Medan is having problems which the manager says that there is no consumer purchase intention and most of the customers are only came from North Sumatra. The population that the writer used is the purchasing customers in UD. Cipta Prima Medan, which is 45 customers. The writer uses convenience sampling technique in which the sample are selected because readily available and convenience. In analyzing data, the writer used some methods such as statistics, normality test, validity test, reliability test, correlation test, determination test, linier regression, and hypothesis test. Based on statistical calculation and analysis, the data is highly valid and the questionnaire is reliable. The Pearson correlation coefficient is 0,87 and the determination is 75.20%. This means that there are high and positive relation between E - Commerce and consumer purchase intention. The linear regression equation of this variable is Y = -3.54 + 1.28X. The Zcount of this skripsi is 5,8 and Ztable 1,96. Since Zcount > Ztable, hence Ha is accepted. This means that E- Commerce has an impact toward Consumer purchase intention at UD. Cipta Prima